Metabolic effects of low glycaemic index diets - Rusu Emilia; Radulian Gabriela; Dragomir Andreea; Posea Mihaela (Nutrition Journal, 2009)
Abstract The persistence of an epidemic of obesity and type 2 diabetes suggests that new nutritional strategies are needed if the epidemic is to be overcome. A promising nutritional approach suggested by this thematic review is metabolic effect of low glycaemic-index diet. The currently available scientific literature shows that low glycaemic-index diets acutely induce a number of favorable effects, such as a rapid weight loss, decrease of fasting glucose and insulin levels, reduction of circulating triglyceride levels and improvement of blood pressure. The long-term effect of the combination of these changes is at present not known. Based on associations between these metabolic parameters and risk of cardiovascular disease, further controlled studies on low-GI diet and metabolic disease are needed.